2020
DOI: 10.1186/s12885-020-06902-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in prostate Cancer-specific mortality in Pennsylvania using Pennsylvania Cancer registry data, 2004–2014

Abstract: Background: Spatial heterogeneity of prostate cancer-specific mortality in Pennsylvania remains unclear. We utilized advanced geospatial survival regressions to examine spatial variation of prostate cancer-specific mortality in PA and evaluate potential effects of individual-and county-level risk factors. Methods: Prostate cancer cases, aged ≥40 years, were identified in the 2004-2014 Pennsylvania Cancer Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Further, there are interactions between these risk factors, particularly with those involving the environment [ 13 , 14 ], whose spatial variation may lead to heterogeneity in the pattern of cancers in a given geographic catchment area. Studies by Wang et al [ 15 , 16 ] found a significant spatial variation of prostate cancer incidence and prostate cancer-specific mortality in Pennsylvania, USA. They evaluated potential effects of individual and county-level risk factors and found that spatial variations in prostate cancer-specific mortality rates existed in Pennsylvania with a particularly high risk in the Pen State catchment area.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there are interactions between these risk factors, particularly with those involving the environment [ 13 , 14 ], whose spatial variation may lead to heterogeneity in the pattern of cancers in a given geographic catchment area. Studies by Wang et al [ 15 , 16 ] found a significant spatial variation of prostate cancer incidence and prostate cancer-specific mortality in Pennsylvania, USA. They evaluated potential effects of individual and county-level risk factors and found that spatial variations in prostate cancer-specific mortality rates existed in Pennsylvania with a particularly high risk in the Pen State catchment area.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there are interactions between these risk factors, particularly with those involving the environment (13,14), whose spatial variation may lead to heterogeneity in the pattern of cancers in a given geographic catchment area. Studies by Wang et al (15,16) found a signi cant spatial variation of prostate cancer incidence and prostate cancer-speci c mortality in Pennsylvania, USA. They evaluated potential effects of individual and county-level risk factors and found that spatial variations in prostate cancer-speci c mortality rates existed in Pennsylvania with a particularly high risk in the Pen State catchment area.…”
Section: Introductionmentioning
confidence: 99%
“…There is a spatial variation in environmental risk factors and this variation may lead to heterogeneity in the pattern of cancers in a given geographic catchment area. Studies by Wang et al (2017) and Wang et al (2020) found a signi cant spatial variation of prostate cancer incidence and prostate cancer-speci c mortality in Pennsylvania, USA. They evaluated potential effects of individual and county-level risk factors and found that spatial variations in prostate cancer-speci c mortality rates existed in Pennsylvania with a particularly high risk in the Pen State catchment area (15,16).…”
mentioning
confidence: 99%
“…Studies by Wang et al (2017) and Wang et al (2020) found a signi cant spatial variation of prostate cancer incidence and prostate cancer-speci c mortality in Pennsylvania, USA. They evaluated potential effects of individual and county-level risk factors and found that spatial variations in prostate cancer-speci c mortality rates existed in Pennsylvania with a particularly high risk in the Pen State catchment area (15,16). County-level health and environmental factors might contribute to spatial heterogeneity in prostate cancer-speci c mortality in the study area.…”
mentioning
confidence: 99%